Extracting Mobility-Lifetime Product in Solar Cell Absorbers Using Quantum Efficiency Analysis. Issue 1771 (18th May 2015) - Poindexter, Jeremy R.; Brandt, Riley E.; Mangan, Niall M.; Buonassisi, Tonio
ABSTRACT: The long-wavelength quantum efficiency (QE) response of photovoltaic absorbers is determined by the length scales for minority carrier collection. However, extracting quantitative measurements of minority carrier mobility-lifetime product ( μτ ) is complicated by uncertainty in other factors such as the depletion width, electric field, and the absorption coefficient. We apply previously developed methods to obtain estimates for μτ in a tin(II) sulfide (SnS) solar cell. We compare three analytic models for the minority carrier collection probability as a function of absorber depth to determine which model most accurately captures the behavior in our devices. For models in which multiple parameters are unconstrained, a random numerical search is used to optimize the fit to experimental QE for SnS. To identify sources of error, we perform a sensitivity analysis by fitting with SCAPS-1D. Our analysis shows that changes in absorption most strongly affect estimates for μτ, highlighting the need to obtain accurate, device-specific absorption data. Further modeling and experimental constraints are required to obtain self-consistent values for μτ that correspond to actual device performance.